PENGARUH KONSUMSI RUMAH TANGGA, INVESTASI TERHADAP PERTUMBUHAN EKONOMI DI PROVINSI JAMBI - Sudirman Sudirman; M Alhudhori (Ekonomis: Journal of Economics and Business, 2018)
This research is research that is literature research where the data used is data which have been researched by previous researcher, this research use time series data year 2005 - 2015. Where purpose of this research to see how influence from free variable (household consumption, investment ) to the dependent variable (economic growth). hypothesis testing the influence of household consumption, investment, there is a significant relationship to economic growth in the province of jambi, this is adjusted to economic theory that economic growth will be explained by investment then this can be proven by using the F-test (collectively) and t-test (partially) with a 95% confidence level or significance level (α = 0.05) then the value of F-table is 4.07 whereas F arithmetic is 9,422 thus the F statistic test criteria stated that F-count (9,422 )> from F-table (4.07), which means rejecting Ho and Ha accepted at a 95% confidence level. This shows that together the independent variables significantly affect the economic growth.Keywords: Economic Growth, Household Consumption, Investment